MODELING OF MANAGEMENT PROCESSES OF THE SYSTEM OF FORMATION OF REFLEXIVE SKILLS IN STUDENTS - Vapayeva Fazilat Shuhratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
To ensure the activity of students in the scientific basis of organizing and increasing the effectiveness of educational processes in the direction of forming and developing reflexive skills in students, actively working with children who have a negative attitude to classes and extracurricular activities. Organization of cooperative educational activities of students, formation of creative approach skills and interests in them is one of the important tasks.